Central bank forecasts of liquidity factors: Quality, publication and the control of the overnight rate - Ulrich Bindseil (European Central Bank (ECB), 2001)
A simple model of the interaction between central bank liquidity management and the inter-bank overnight rate is suggested which allows analysing the publication of forecasts of liquidity factors by the European Central Bank adopted in June 2000. The paper argues that the main practical advantage of the publication of these forecasts is that it makes the signal extraction problem with regard to the central bank's intentions trivial and hence allows establishing a superior behavioural equilibrium between the central bank and the money market participants. In this equilibrium, the central bank can achieve a better steering of overnight rates than under private autonomous factor forecasts, depending of course also on the quality of liquidity forecasts. It is furthermore shown that the publication of an average of autonomous factors, such as adopted by the ECB, is, at least within the model presented, superior to the separate publication of autonomous factors for each single day
Keywords: D84; E52; 330; forecasts of liquidity factors